What are the post-ablation insular residual electrograms in the posterior left pulmonary veins electrically connected to? - Kohki Nakamura; Masateru Takigawa; Takehito Sasaki; Kentaro Minami; Shigeto Naito (Indian Pacing and Electrophysiology Journal, 2021)
A 67-year-old man underwent a third ablation procedure for a recurrent atrial tachycardia (AT) after an extensive pulmonary vein (PV) isolation, linear ablation along the left atrial (LA) roof and posterolateral mitral isthmus (MI), and defragmentation of persistent atrial fibrillation and an induced perimitral AT. High-resolution mapping during the clinical AT using the Rhythmia system (Boston Scientific) suggested that the AT was a ridge-related reentrant AT and exhibited a reconnection of the left PVs (LPVs). The residual electrograms in the posterior LPVs were surrounded by endocardial scar, which was like an island consisting of residual LPV electrograms. Retrograde venography of the vein of Marshall (VOM) demonstrated that the VOM reached the posterior left superior PV through the ridge between the LA appendage and left inferior PV and then the LPV carina. An ethanol infusion into the VOM resulted in a simultaneous AT termination and complete electrical isolation of the LPVs, that is, the disappearance of the residual LPV electrograms. The insular residual LPV electrograms in the present case did not appear to be endocardially connected to the LA, because the LPV electrograms were surrounded by endocardial scar and there was a large time gap between the earliest activation in the posterior LPVs and activation in the surrounding area. The VOM course on the venography and elimination of the residual LPV electrograms with an ethanol infusion into the VOM suggested that the insular residual LPV electrograms were electrically connected to the posterolateral LA via the VOM and its branches.